Learning curve for robot-assisted laparoscopic radical prostatectomy in a large prospective multicentre study. (4th May 2022) - Bock, David; Nyberg, Martin; Lantz, Anna; Carlsson, Sigrid V.; Sjoberg, Daniel D.; Carlsson, Stefan; Stranne, Johan; Steineck, Gunnar; Wiklund, Peter; Haglind, Eva; Bjartell, Anders
Abstract: Objective: Differences in outcome after radical prostatectomy for prostate cancer can partly be explained by intersurgeon differences, where degree of experience is one important aspect. This study aims to define the learning curve of robot-assisted laparoscopic prostatectomy (RALP) regarding oncological and functional outcomes. Materials and methods: Out of 4003 enrolled patients in the LAPPRO trial, 3583 met the inclusion criteria, of whom 885 were operated on by an open technique. In total, 2672 patients with clinically localized prostate cancer from seven Swedish centres were operated on by RALP and followed for 8 years (LAPPRO trial). Oncological outcomes were pathology-reported surgical margins and biochemical recurrence at 8 years. Functional outcomes included patient-reported urinary incontinence and erectile dysfunction at 3, 12 and 24 months. Experience was surgeon-reported experience before and during the study. The relationship between surgeon experience and functional outcomes and surgical margin status was analysed by mixed-effects logistic regression. Biochemical recurrence was analysed by Cox regression, with robust standard errors. Results: The learning curve for positive surgical margins was relatively flat, with rates of 21% for surgeons who had performed 0–74 cases and 24% for surgeons with > 300 cases. Biochemical recurrence at 4 years was 11% (0–74 cases) and 13% (> 300 cases). Incontinence was stable over the learning curve, but erectile function improved at 2 years, from 38% (0–74 cases) to 53% (> 300 cases). Conclusions: Analysis of the learning curve for surgeons performing RALP showed that erectile function improved with increasing number of procedures, which was not the case for oncological outcomes.